COMPARING SPOKEN LANGUAGE PERFORMANCE ACROSS PROFICIENCY LEVELS: THE IMPACT OF TASK TYPES ON LOW AND HIGH PROFICIENCY LEARNERS - Ramadhani, Aulia Fitri; Mahpul, Mahpul; Sukirlan, Muhammad (Universitas PGRI Sumatera Barat, 2025)
This study investigates how task complexity affects students’ speaking performance based on their English proficiency levels. It was conducted at SMA N 9 Bandar Lampung in the 2024/2025 academic year with 31 eleventh-grade students, divided into low (n = 16) and high (n = 15) proficiency groups. Each student completed a simple and a complex speaking task. The tasks were based on task-based language teaching (TBLT) and aligned with the curriculum. Using Two-Way ANOVA, the results showed that both task complexity and proficiency level significantly influenced speaking performance (p<0.05). High proficiency students outperformed low proficiency students in all aspects: complexity (M = 3.85 vs. 2.97), accuracy (M = 4.12 vs. 3.21), and fluency (M = 4.08 vs. 3.05). A significant interaction was also found, meaning task complexity affected students differently depending on their proficiency. This study shows that speaking tasks should be adjusted to students’ proficiency levels to improve learning outcomes.